Influence of La addition on Fe-rich intermetallic phases formation and mechanical properties of Al-7Si-4Cu-0.35Mg-0.2Fe alloys prepared by squeeze casting. (February 2023) - Zhao, Biwei; Xing, Shuming; Shan, Aili; Yan, Guangyuan; Jiang, Xiaolong
Abstract: Brittle β-Al5 FeSi (β-Fe) intermetallic phases directly affect the mechanical properties of Al–Si alloys; thus, it is essential to modify these phases. Scanning electron microscope analysis showed that rare earth Lanthanum (La) additions (0, 0.15, 0.30 and 0.50 wt%) had a refining effect on β-Fe phases in Al–7Si–4Cu-0.35Mg-0.2Fe (wt.%) alloys prepared by squeeze casting. The underlying refinement mechanisms of rare earth La on the β-Fe were discussed in terms of experimental observations, nucleation thermodynamics and growth kinetics. For nucleation thermodynamics, La additions could induce the formation of La-rich intermetallic phases Al4 Cu2 SiLa with orthorhombic structure. Because β-Fe nuclei had a good lattice matching and epitaxial relationship with the Al4 Cu2 SiLa phases, the Al4 Cu2 SiLa provided energetically favorable nucleation sites for β-Fe and greatly promoted the nucleation of β-Fe in alloys. Meanwhile, the added La atoms could restrain the diffusion of atoms to the solid/liquid interface front and alter the β-Fe interfacial structure and energy, therefore restricting the β-Fe growth. Furthermore, β-Fe/Al4 Cu2 SiLa grew into side-by-side and cross-like morphologies, and its growth behaviors were controlled by solute concentration and anisotropy of the solid-liquid interfacial energy in a cooperative eutectic reaction. In addition, different fracture behaviors from brittle fracture to mixed ductile fracture and quasi-cleavage brittle fracture were also illustrated with increasing La addition, and these fracture behaviors were influenced by the characteristics of brittle La-rich and β-Fe intermetallic phases. When the addition of La was increased to 0.3 wt% and 0.5 wt%, it occurred quasi-cleavage brittle fracture, which was caused by the precipitation of coarse plate-like La-rich phases. Highlights: La addition modifies the size and thickness of Al5 FeSi phases. Al4 Cu2 SiLa particles provide nucleation sites for Al5 FeSi. Eutectic Al5 FeSi/Al4 Cu2 SiLa shows side-by-side or crossed morphology. Growth of Al5 FeSi relies on solute content and S/L anisotropic interfacial energy.